The Brazilian psychiatric reform: historical and technical-supportive aspects of experiences carried out in the cities of São Paulo, Santos and Campinas - Cristina Amélia Luzio; Solange L'Abbate; Carmenlicia Bertoncini Gonçalez (Interface: Comunicação, Saúde, Educação, 2007)
The Brazilian psychiatric reform: historical and technical-supportive aspects of experiences carried out in the cities of São Paulo (capital), Santos and Campinas, in order to understand their material, social and political impacts, the progress in the process of breaking away from the psychiatric ward model, and the establishment of creative and productive groups, required to build up the psychosocial treatment in regard to mental health, as well as to evaluate the contribution that the SUS (Brazilian Public Health System) had on the psychiatric reform in the mentioned cities. The research, which is the basis of this paper, is part of a thesis regarding mental health care, whereby the innovative projects implemented in those cities served as framework and basis for comparison to analyze mental health policy in small and medium-sized cities and towns in the state of São Paulo.